Relationship of third molar movement during orthodontic treatment and root angulation - Morteza Oshagh; Nariman Iraji Nasrabadi (Wolters Kluwer Medknow Publications, 2012)
Background: Curved roots of teeth might cause difficulty in root canal treatment and removal. Beside genetic factors, root morphology of the third molars is affected by environmental factors such as mesial migration. However no studies examine the relation between the amount of third molars' movement and their root angles. The purpose of this study was to evaluate the relation between the amount of third molar movement during orthodontic treatment and the angulation of third molar roots. Materials and Methods: The records of 39 patients who had apical closure after orthodontic treatment were evaluated. Root curvature was measured on panoramics using the angle between an occlusal reference line and central line of the most apical ninth of the root. The amount of tooth movement of third molars was measured on the pre- and post- treatment lateral cephalometric radiographs by measuring tooth distance from a perpendicular line. Pearson correlation analysis was preformed to obtain relation of the amount of third molar's movement and its root angulation. Results: In maxillary arch the correlation between tooth movement and root angulation was positive and not significant relation but in mandibular arch this relation was negative and not significant. ( P > 0.05) Conclusion: The relation between the amount of third molar movement and its root angulation was not statistically significant. Therefore movement of third molars during orthodontic treatment should not be assumed as an etiologic factor of root angulations.